أثر استخدام أساليب التقويم الحقيقى فى مادة العلوم على تنمية التحصيل الدراسى والتفكير الناقد والمهارات الحياتية لدى طلاب الصف الثانى المتوسط - الرضيان، خالد بن إبراهيم; الشايع، فهد بن سليمان (جامعة طيبة - كلية التربية, 2010)
هدف هذا البحث إلى الكشف عن أثر استخدام أساليب التقويم الحقيقي في مادة العلوم على تنمية التحصيل الدراسي، والتفكير الناقد، والمهارات الحياتية لدى طلاب الصف الثاني متوسط بمدينة الرياض، واستُخدِمَ المنهج المزيج؛ والذي ضم المنهج التجريبي الحقيقي المتمثل في التصميم القائم على وجود مجموعة ضابطة مع اختبار بعدي فقط، وكذلك الأسلوب الاستقرائي في المنهج النوعي (الكيفي). وتكونت عينة الدراسة من 59 طالباً يمثلون فصلين من فصول الصف الثاني المتوسط الثلاثة بمدرسة ابن الرومي المتوسطة بالرياض، حيث تم توزيع الطلاب عشوائياً على فصول الصف الثاني المتوسط في بداية العام الدراسي بالتنسيق مع إدارة المدرسة، كما تم اختيار الصفوف عشوائياً لتمثل المجموعة التجريبية والضابطة، وقد مثل المجموعة التجريبية 29 طالباً، والمجموعة الضابطة 30 طالباً. وأُعِدَ للبحث من الأدوات: اختبار تحصيلي، واختبار التفكير الناقد، وبطاقة المقابلة. \ وأظهرت نتائج البحث عن وجود فروق ذات دلالة إحصائية بين متوسطي درجات تحصيل طلاب المجموعتين التجريبية والضابطة لصالح المجموعة التجريبية، ووجود فروق ذات دلالة إحصائية بين متوسطي أداء طلاب المجموعتين التجريبية والضابطة في اختبار التفكير الناقد لصالح المجموعة التجريبية. كما أظهرت نتائج البحث أن المهارات الحياتية التي اكتسبها الطلاب بعد أن طبقت عليهم أساليب التقويم الحقيقي هي: مهارات المسئولية (الاعتماد على النفس، الثقة بالنفس، اتخاذ القرار، تحمل المسئولية، التقويم الذاتي)، ومهارات العمل (التخطيط، التعاون، الدقة، التنظيم)، ومهارات التواصل (التواصل الكتابي واللفظي، إبداء الرأي). وفي ضوء النتائج السابقة أوصى البحث بالتأكيد على استخدام أساليب التقويم الحقيقي (ملف التعلم، الملاحظة، خريطة المفاهيم) عند تقويم الطلاب في مادة العلوم، وأن يتم تدريب معلمي العلوم قبل الخدمة وأثنائها على استخدامها. This research aimed at investigating the impact of using authentic assessment methods on science academic achievement, critical thinking and life skills of the students of the second intermediate Class (8thgrade) in Riyadh, Saudi Arabia. A mixed method including true experimental designed qualitative method was used. The study sample comprised (59) students representing two of the three 8thgrade classes at Ibn Al-Rumi Intermediate School in Riyadh. The Students were randomly assigned to the classes at the beginning of the year in coordination with the school administration. \ The classes were randomly selected to represent the experimental and control groups. The experimental group comprised (29) students and the control group comprised (30) students. The research instruments included: an achievement test, a critical thinking test and students interviews. \ The findings revealed that there were statistically significant differences between the achievement scores of the experimental and control groups in favor of the experimental group. Also, there were statistically significant differences between the performance scores of experimental and control groups in the critical thinking test in favor of the experimental group. \ The findings also showed that the life skills acquired by students who underwent the authentic assessment methods, were: (1) the responsibility skills (self-dependence, self-confidence, decision-making, self-responsibility and self-evaluation), (2) the work skills (planning, cooperation, precision and organization) and (3) the communication skills (written and verbal communication, opinion expression). In light of the results, this research recommended the use of learning portfolios, observation and concept maps when evaluating science students, teachers should receive training on authentic assessment methods.
Keywords: طرق التدريس -- العلوم -- أساليب التقويم الحقيقى -- التفكير الناقد -- المهارات الحياتية -- التحصيل الدراسى -- الصف الثانى المتوسط